2009
DOI: 10.1016/j.jmb.2009.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism of Bacterial Flagellar Motor Switching

Abstract: SummaryThe high-resolution structures of nearly all the proteins that comprise the bacterial flagellar motor switch complex have been solved; yet a clear picture of the switching mechanism has not emerged. Here we use NMR to characterize the interaction modes and solution properties of a number of these proteins, including several soluble fragments of the flagellar motor proteins FliM and FliG and the response-regulator CheY. We find that the switch signal, activated CheY, binds to a previously unidentified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 58 publications
1
90
1
Order By: Relevance
“…Both of these proteins function in controlling the direction of flagellar rotation (50)(51)(52)(53), and single point mutations in FliM have been shown to restore swarming motility in a chemotaxis-deficient mutant of Salmonella enterica (52). We hypothesize that SNPs in these genes led to enhanced swarming motility of the corresponding revertants by direct manipulation of the flagellar motor.…”
Section: Resultsmentioning
confidence: 95%
“…Both of these proteins function in controlling the direction of flagellar rotation (50)(51)(52)(53), and single point mutations in FliM have been shown to restore swarming motility in a chemotaxis-deficient mutant of Salmonella enterica (52). We hypothesize that SNPs in these genes led to enhanced swarming motility of the corresponding revertants by direct manipulation of the flagellar motor.…”
Section: Resultsmentioning
confidence: 95%
“…FliM contains an amino-terminal CheY-binding motif (FliMn) that recruits CheY-P to the motor (25)(26)(27). NMR studies have shown that in addition to CheY-P binding to the N-terminal motif, it also interacts with the middle domain of FliM, albeit weakly (29). The crystal structure of the middle domain of FliM (FliMm) reveals a topology similar to CheC (30).…”
mentioning
confidence: 99%
“…In most species, the motor can rotate either clockwise (CW) or counterclockwise (CCW), and cells can direct their movement toward favorable environments or away from unfavorable ones by controlling the direction of motor rotation (1)(2)(3)(4). The molecular mechanism of the motor is not understood fully, but proteins with key roles in rotation and direction switching have been identified, and some general aspects of the mechanism have been established (5,6).…”
mentioning
confidence: 99%